Synthesis and application of surfactants coated magnetite nanoparticles for demulsification of crude oil in water emulsion - Yau, X.H. (American Institute of Physics Inc., 2017)
Magnetite nanoparticles were synthesized through co-precipitation method, in which surfactant such as polyvinylpyrrolidone (PVP) and sodium dodecyl benzene sulfonate (SDBS) were applied as stabilizing agent. Various techniques were employed to characterize the synthesized magnetite nanoparticles. Magnetite nanoparticles with spinel structure are successfully synthesized and confirmed by X-ray diffraction (XRD). X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) results proved that surface of magnetite nanoparticles were successfully coated with PVP and SDBS. From the transmission electron microscope (TEM), it showed that surfactant coated magnetite nanoparticles possess smaller particle size than that of bare magnetite nanoparticles. In comparison with SDBS, PVP has a better capping efficiency and the PVP coated magnetite nanoparticles have an average particle size of 10.8 nm. In addition, surfactant coated magnetite nanoparticles also exhibited lower value of saturation magnetization (Ms). Lower value of Ms might be attributed to the small sized nanoparticles. All magnetite nanoparticles synthesized with and without surfactant showed superparamagnetic behaviour. Bare and surfactant coated magnetite nanoparticles have been utilized as a demulsifier for crude oil in water emulsion. Those nanoparticles that produced using SDBS (ED= 87) showed higher efficiency than that of PVP coated (ED=80) and bare magnetite nanoparticles (ED=85) in demulsification tests. © 2017 Author(s).